The introduction to the docetism controversy - Meirbaev, Bekzhan; Badagulova, Zhansaya (ҚазҰУ Хабаршысы. Дінтану сериясы, 2016)
To control the masses, the political organization of the church declared that salvation can only be achieved through religious rituals and priesthood. Salvation through the personal mystical experience with Christ outside the organized church has been thrown out. Christian Gnosticism was obliterated and relatively little historical and theological information was left to fully understand early Christian history. Docetism as one of the earliest Christian Gnostic movements eventually was eradicated from Christian history. According to the historians Docetic Gnostic wrote his own Gospel including The Acts John and, as mentioned previously, The Gospel of Peter. But genuinely their attitude opposite the Church’s main ideology concerning Jesus and his personality which leads to cruel excommunication of Docetism.